Marxismo negro e direito: análise jurídico-política da práxis negra revolucionária - Daniel Vitor de Castro (2024)
This research analyzes the theoretical-political tradition of Black Marxism through the lens of Marxist criticism of law taken by revolutionary Marxism. We characterize so-called Black Marxism as the contribution of revolutionary black intellectuals who find in Marxism the necessary tool for analyzing the different social forms of racism and colonialism and for the strategic political action of social struggle. We present the tension within Marxist legal theory between the critique of the legal form and the imperative of class struggle as a disagreement of the times of critique and strategy. We propose the notion of political broken-time and praxis to mobilize syntheses, arguing that the Marxist critique of legal reason is at once a materialist analysis of the relational nature of law and a social theory of its political uses by strategic action. From the legal-political analysis of different socio-historical frameworks of Black Marxism, we argue that revolutionary Black praxis combines a materialist analysis of the relationship between law and racism, a structural critique of the legal form, and the political formulation of tactical-pedagogical uses of law for the strategic action of revolutionary anti-racism.